Detection of Potential Chloroplastic Substrates for Polyphenol Oxidase Suggests a Role in Undamaged Leaves - Boeckx, Tinne; Winters, Ana; Webb, K. Judith; Kingston-Smith, Alison H. (Frontiers in Plant Science, 2017)
Polyphenol oxidases (PPOs) have a recognized role during pathogen and arthropod attack. As an immediate consequence of such wounding, cellular compartmentation is destroyed allowing the chloroplastic PPO enzyme to interact with vacuolar substrates catalysing the oxidation of monophenols and/ or o-diphenols to o-diquinones. This ultimately results in a reduction in the nutritional value of wounded tissue through the formation of non-digestible secondary melanin pigments. However the chloroplastic location of PPO enzyme could indicate a role for PPO in undamaged tissues. In this study, a wild-type red clover population exhibiting high leaf PPO activity had significantly higher yield than a low leaf PPO mutant population while leaf isoflavonoids and hydroxycinnammates (PPO substrates) accumulated at similar levels in these plants. These data suggest that the presence of leaf PPO activity affects plant vigour. Understanding how this advantage is conferred requires knowledge of the cellular mechanism, including intra-organellar substrates. Here we present evidence of candidate PPO substrates within chloroplasts of wild-type red clover, including the monophenolic acid, coumaroyl malate and low levels of the diphenolic acid, phaselic acid (caffeoyl malate). Interestingly, chloroplastic phaselic acid concentration increased significantly under certain growth conditions. We discuss the implications of this in regard to a potential role for chloroplastic PPO in undamaged leaves.